Ruang Guru dan Tenaga Kependidikan sebagai Game Changer dalam Pengembangan Keterampilan Guru - Syaiful Arif, Ahmad Nurjihad; Sholihah, Husna Imro'athush; Nurwulandari, Ika (Universitas Muhammadiyah Magelang, 2025)
The purpose of this research is to identify the realization of the Teacher and Education Personnel Room (GTK) as a Game Changer in teacher skill development, identify challenges and obstacles and identify strategies. This study uses a qualitative research type with a case study approach. Data collection uses observation techniques in the teacher's room, interviews with all teachers and principals, documentation in the form of documents (learning books, assessments, and pictures), and questionnaires intended for all teachers. The results of the study show that the realization of the Teacher and Education Personnel Room (GTK) at SD Negeri 1 Gandu in the teacher learning process adopts various teaching materials, inspirational videos to improve teacher skills and teacher competence. The existence of the Teacher and Education Staff Room is very helpful for educators. Thus, the realization of a strategic Teacher and Education Personnel Space and effective realization has great potential to improve teacher skill development. This is not just an additional facility, but an important platform in creating competent, innovative, and motivated teachers, which will ultimately improve the overall quality of education. In addition, strategies to maximize the use of the Teacher and Education Personnel (GTK) space at SD Negeri 1 Gandu such as infrastructure support with resources, utilizing community features, and increasing digital initiatives.